Targeted delivery of polypeptide nanoparticle for treatment of traumatic brain injury - Wu P (Dove Medical Press, 2019)
Peng Wu,1 Haitian Zhao,2 Xingchun Gou,3 Xingwang Wu,4 Shenqi Zhang,1 Gang Deng,1 Qianxue Chen11Department of Neurosurgery, Renmin Hospital of Wuhan University, Wuhan, Hubei 430060, People’s Republic of China; 2School of Chemistry and Chemical Engineering, Harbin Institute of Technology, Harbin, 150001, People’s Republic of China; 3Shaanxi Key Laboratory of Brain Disorders & Institute of Basic and Translational Medicine, Xi’an Medical University, Xi’an 710021, People’s Republic of China; 4Department of Radiology, The First Affiliated Hospital of Anhui Medical University, Hefei, Anhui, 230020, People’s Republic of ChinaBackground and purpose: Traumatic brain injury (TBI) is a major disease without effective treatment. Recently, Tat-NR2B9c peptide emerged as a promising neuroprotective agent, but limited in clinical translation by it low brain penetrability. We synthesized Tat-NR2B9c loaded self-assembled activatable protein nanoparticles, termed TN-APNPs, and demonstrated that TN-APNPs enhanced the delivery of Tat-NR2B9c to the brain lesion in stroke. Herein we developed a novel approach to further engineering TN-APNPs for targeted delivery of Tat-NR2B9c to the injured brain with enhanced efficiency through conjugation of CAQK or CCAQK, a short peptide.Methods: Short peptide-conjugated TN-APNPs were synthesized by conjugated with CAQK or CCAQK via a click condensation reaction with CBT, then analyzed by dynamic light scattering, transmission electron microscopy and thrombin responsive assay. Characterization of short peptide-conjugated TN-APNPs were investigated by using cell excitotoxicity assay and transwell blood-brain-barrier model in vitro, and pharmacokinetics, IVIS imaging system and confocal analysis in TBI-bearing mice. Evaluation of therapeutic effects were analyzed by H&E staining, Elevated Plus Maze analysis and Rotarod test.Results: CAQK-conjugated TN-APNPs (C-TN-APNPs) and CCAQK-conjugated TN-APNPs (CC-TN-APNPs) were spherical in morphology and 30 nm in diameter. In vitro studies revealed that TN-APNPs, C-TN-APNPs and CC-TN-APNPs were responsive to thrombin cleavage, reduced the cytotoxicity of Tat-NR2B9c, and increased BBB permeability of Tat-NR2B9c. CC-TN-APNPs demonstrated the better circulation time, better targeting ability and penetrating efficiency to the injured brain, and better therapeutic benefits in vivo studies.Conclusion: This study demonstrated CC-TN-APNPs as a promising therapeutic for clinical management of TBI.Keywords: traumatic brain injury, Nanoparticle, Tat-NR2B9c, CAQK, CCAQK